Reconciling competing policy approaches to wildlife crime - Felbab-Brown, Vanda (Wildlife crime, 2018)
Conservationists may be roughly divided into three groups whose approaches to wildlife protection appear at odds with one another. Animal rights activists are drawn to a straightforward prohibitionist approach: simply ban the trade in wild species. An opposed constituency argues that these creatures will not survive if they have no economic purpose, and that a regulated international trade is essential for conservation. A third group puts the empowerment of local communities first, rejecting what they see as a neo-colonial dimension to the wildlife protection discourse. The author argues that, as is the case with illegal drugs, the appropriate policy approach depends on the context. There can be no shortcut for understanding the particular dynamics of each wildlife trafficking flow, and pragmatism must trump ideology if we are to have any hope of preserving vulnerable species.